Comparative investigations on hull line optimization based on traditional and fully parametric methods for saving energy - Cheng, Xuankai; Wang, Dong; Huang, Xinhui; Yan, Xu; Dou, Peng; Ji, Renwei (Frontiers in Energy Research, 2024)
The new regulations on ship energy efficiency proposed by the International Maritime Organization had a significant impact on the shipping industry and shipbuilding industry. Improving the speed performance of ships was an effective approach to meet the requirements of energy conservation and emission reduction, reduce ship energy consumption and operating costs, and strengthen the market competitiveness of the ship enterprises. One of the improvement methods of the ship speed performance mainly was reducing the ship resistance. The main approach was to optimize the principal dimensions and hull lines of ships.Taking the research and development of a feeder as an example, the application of fully parametric optimization method in the optimization of ship hull lines was described in detail. The parent ship was selected from the ship database, which has an excellent speed performance. The parent ship was simply transformed to meet the requirements of the target ship; The traditional optimization method was used to optimize the hull lines to reduce the hull resistance as much as possible, and a hull line with the best resistance performance was obtained; Based on the initial hull lines that met the requirements, the fully parametric model of the hull was established, and the fully parametric optimization method was used to optimize the hull with the best resistance performance; Experiments were carried out in the towing tank and the resistance results of the two types of ships were gotten. The simulation of computational fluid dynamics (CFD) and model test had good consistency and it was found that the hull lines optimized by fully parameterization had better performance than those optimized by the traditional method; The fully parametric hull line optimization method was effective in optimizing hull lines, and it also could reduce the excessive dependence of research personnel on the parent ship and design experience.